Investigating the Reasons for the Integration of Schools in Nagykanizsa (Training and Practice : Journal of Educational Sciences, 2015)
In my study I am searching for the answer on the question what economic considerations or organizational transformations justified the integration of two significant schools in Nagykanizsa. My study reveals the economic reasons for the integration as well as the correlations. Besides the economic research the aim of the study was to show how the teachers of both schools were affected by the integration. As a consequence of this complex research I have discovered cause and effect relationships and offer suggestions on a more effective operation.